- 2 x + y = - 3

- x + 2 y = - 3

a. (–3, –9)

b. (–21, –9)

c. (3, 3)

d. (0, 2)

To eliminate y, multiply eq.1 by 2

- 4 x + 2y = - 6

x=1So y = -3 +2 = -1

The points are (1,-1).

Please check if the equations are correct.

the second equation is - x + 2 y = 3

- x + 2 y = 3

x=3So y = -3 +6 = 3

The points are (3,3).

Please let me know if you have any other questions and best me if you are satisfactory.

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up